2012
DOI: 10.1161/hypertensionaha.111.182154
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Induced Hypertension Is Modulated by Nuclear Factor-κB in the Paraventricular Nucleus

Abstract: Hypertension is considered a low-grade inflammatory condition and understanding the role of transcription factors in guiding this response is pertinent. A prominent transcription factor that governs inflammatory responses and has become a focal point in hypertensive research is Nuclear Factor-kappaB (NFκB). Within the hypothalamic paraventricular nucleus (PVN), a known brain cardio-regulatory center, NFκB becomes potentially even more important in ultimately coordinating the systemic hypertensive response. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
128
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 51 publications
(59 reference statements)
3
128
0
2
Order By: Relevance
“…PVN was isolated from frozen brain sections using a Stoelting brain punch (Stoelting) and, then, the tissue was homogenized with RIPA lysis buffer, as previously described (2,7,18,39). The protein concentration was measured using a bicinchoninic acid (BCA) protein assay kit (Pierce).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PVN was isolated from frozen brain sections using a Stoelting brain punch (Stoelting) and, then, the tissue was homogenized with RIPA lysis buffer, as previously described (2,7,18,39). The protein concentration was measured using a bicinchoninic acid (BCA) protein assay kit (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was demonstrated that acute microinjection of proinflammatory molecules into the PVN of normotensive rats causes elevation of both arterial pressure and renal sympathetic nerve activity (38). On the other hand, chronic inhibition of proinflammatory signaling in the brain decreased arterial pressure and renal sympathetic nerve activity, and reversed the deleterious cardiac remodeling in hypertensive rats (7,13,18,39). Therefore, brain inflammation emerges as a central factor that contributes to autonomic and cardiovascular abnormalities in hypertension.…”
mentioning
confidence: 99%
“…HEART FAILURE AS CIRCULATORY HOMEOSTASIS FAILURE pro-inflammatory cytokines, [65][66][67][68][69] perivascular macrophages, 70,71) transcription factor nuclear factor kappa B, 72) and microglial cytokines 73,74) have been reported as being important factors of sympathoexcitation.…”
Section: Central Mechanisms Of Sympathoexcitation In Heart Failurementioning
confidence: 99%
“…More recently, experiments suggested that cytokines as neuromodulators exert their action on cardiovascular control through interaction with the brain angiotensin system: pretreatment with either IL-1β or TNF-α enhances the pressor response to the central infusion of angiotensin II [73] ; the pressor and dipsogenic effects of angiotensin II in mice require the presence of TNF-α [74] ; blockade of NF-κB in brain ameliorates the development of AngII-induced hypertension, and reduces the expression of angiotensin II type 1 receptors in the heart and the PVN [75] .…”
Section: Brain Cytokines Act As Executors In the Association Between mentioning
confidence: 99%